(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
This article explores the evolving role of Advanced Practice Nurses (APNs) in pre-hospital care and the benefits of collaborative approaches with paramedics. It discusses the historical context, shifting paradigms, and inter-professional collaboration between APNs and paramedics in delivering emergency medical services. The scope of practice for APNs in pre-hospital care, including assessment, triage, advanced interventions, and patient education, is delineated. Training programs, simulation-based learning, benefits, challenges, and future directions are also discussed.